Knowledge about nicotine among HIV-positive smokers: Implications for tobacco regulatory science policy. (February 2017) - Pacek, Lauren R.; Rass, Olga; Johnson, Matthew W.
Abstract: The present paper describes the general knowledge of smoking and nicotine among a sample of current smokers living with HIV ( n = 271) who were recruited via Amazon Mechanical Turk. Descriptive statistics were used to report sociodemographic and smoking characteristics, as well as knowledge about smoking and nicotine. The sample was comprised of relatively light smokers, both in terms of cigarettes per day ( M = 8.1, SD = 9.7) and dependence (67.5% had low dependence according to the Heaviness of Smoking Index). The majority of participants correctly identified smoking as being a potential cause of various smoking-related conditions and correctly identified constituents in cigarette smoke. However, a majority of participants also misattributed nicotine as being a potential cause of smoking-related illness. Accurate knowledge about nicotine was low. These misperceptions are of particular concern for vulnerable populations, such as persons living with HIV, who are disproportionately burdened by the prevalence of smoking and associated morbidities and mortality. These misperceptions could have unintended consequences in the wake of a potential nicotine reduction policy, such that reduced nicotine content products are perceived as safer than normal nicotine content products currently available for sale. Additionally, incorrect knowledge about nicotine has implications for the uptake and continued use of nicotine replacement therapy. Highlights: Most participants identified smoking as a cause of smoking-related morbidity. Most participants misattributed nicotine as causing smoking-related morbidity. Misperceptions about nicotine have implications for potential tobacco regulations.